1993
DOI: 10.1016/s0022-5347(17)35388-0
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Verapamil on Shock Wave Induced Renal Tubular Dysfunction

Abstract: In a prospective randomized study, the effects of the calcium entry blocker verapamil on shock wave induced tubular impairment were examined. A total of 24 patients with renal pelvis or caliceal stones undergoing anesthesia-free extracorporeal shock wave lithotripsy (ESWL*) without auxiliary measures was randomly assigned to the verapamil group (12) or the control group (12). Four doses of verapamil (80 mg. each) were given orally starting the night before ESWL. Controls received no medication. To assess renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Since different treatment parameters as impulse rate and generator vol tage were not present in this study and proteinuria and enzymuria before ESWL, marking the performance status of the tubules, were not different, we conclude that 1,4-dihydropyridine nifedipine could reduce the damaging effect of high-energy shock waves on renal tubular cells. The magnitude of limitation of shock-wave-induced dam age was similar to that which we observed by the applica tion of phenylalkylamine verapamil [10,11], Obviously, this protective effect is not restricted to one subgroup of calcium entry blockers.…”
Section: The Treatment Conditions Of Eswl (Impulse Rate and Generatorsupporting
confidence: 84%
“…Since different treatment parameters as impulse rate and generator vol tage were not present in this study and proteinuria and enzymuria before ESWL, marking the performance status of the tubules, were not different, we conclude that 1,4-dihydropyridine nifedipine could reduce the damaging effect of high-energy shock waves on renal tubular cells. The magnitude of limitation of shock-wave-induced dam age was similar to that which we observed by the applica tion of phenylalkylamine verapamil [10,11], Obviously, this protective effect is not restricted to one subgroup of calcium entry blockers.…”
Section: The Treatment Conditions Of Eswl (Impulse Rate and Generatorsupporting
confidence: 84%
“…Due to a lack of suitable techniques, the mechanisms responsible for such redistribution are not fully understood. It has been demonstrated that vasoactive substances may have an influence on the observed responses (141). In a subsequent study (17), it was shown that aminophylline abolished the drop in cortical flow with no significant change in the medulla.…”
Section: Techniques Based On Endogenous Contrast Mechanismsmentioning
confidence: 95%
“…They considered that these medicines reduced the effects of the reactive oxygen species on tissues (24). Strohmeier et al studied the effects of verapamil (a CCB) and nifedipine on SWL-treated patients and evaluated the tubular excretion markers after SWL treatment which indicated that these CCBs had protective effects on tubular injury and dysfunction of tubular excretion (5,25).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is associated with both short-and long-term risks of renal and extra renal complications (1)(2)(3). Several mechanisms, such as cavitation bubbles, temporary decrease of renal perfusion and ischemia-reperfusion (I/R) injury, are responsible for renal injury during SWL (4)(5)(6). New generation SWL devices are clinically used to decrease complication rates (1).…”
Section: Introductionmentioning
confidence: 99%